SN 2012fr: Ultraviolet, Optical, and Near-infrared Light Curves of a Type Ia Supernova Observed within a Day of Explosion - Contreras, Carlos (2018)
We present detailed ultraviolet, optical, and near-infrared light curves of the Type Ia supernova (SN) 2012fr, which exploded in the Fornax cluster member NGC 1365. These precise high-cadence light curves provide a dense coverage of the flux evolution from −12 to +140 days with respect to the epoch of B-band maximum (tBmax). Supplementary imaging at the earliest epochs reveals an initial slow and nearly linear rise in luminosity with a duration of ∼2.5 days, followed by a faster rising phase that is well reproduced by an explosion model with a moderate amount of 56Ni mixing in the ejecta. From our analysis of the light curves, we conclude that: (i) the explosion occurred <22 hr before the first detection of the supernova, (ii) the rise time to peak bolometric (λ > 1800 Å) luminosity was 16.5 ± 0.6 days, (iii) the supernova suffered little or no host-galaxy dust reddening, (iv) the peak luminosity in both the optical and near-infrared was consistent with the bright end of normal Type Ia diversity, and (v) 0.60 ± 0.15 M⊙ of 56Ni was synthesized in the explosion. Despite its normal luminosity, SN 2012fr displayed unusually prevalent high-velocity Ca II and Si II absorption features, and a nearly constant photospheric velocity of the Si II λ6355 line at ∼12,000 km s-1 that began ∼5 days before tBmax. We also highlight some of the other peculiarities in the early phase photometry and the spectral evolution. SN 2012fr also adds to a growing number of Type Ia supernovae that are hosted by galaxies with direct Cepheid distance measurements.